Dust Cleaning System on Panel PET Preform Injection Machine BM500 - Muhammad Syaiful Azis; Indah Sulistiyowati; Akhmad Ahfas; Izza Anshory (Procedia of Engineering and Life Science, 2022)
Dust Cleaning System on Panel Injection Machine BM500 PET preforms. The clean machine panel is essential so that performance and safety are maintained. Dust that sticks to electrical components such as contactors, servo drives, solid-state relays, PLCs, and several other components causes overheating. Dust attached to the conductors of electrical components will burn and become carbon which bridges the emergence of sparks. To reduce the risk of damage to electrical equipment on the injection machine, an automatic dust cleaning system is designed. This system uses a GP2Y1010AU0F dust sensor, a DHT 22 sensor to detect temperature and humidity, Arduino Uno microcontroller, 16x2 LCD, L298N driver, DC motor, fan, solenoid valve and utilizes high-pressure air to spray dust inside the panel which is then sucked in with a fan and collected in a dust bag. From the results of the trial installation of this system with 10 times of data collection for 4 hours 30 minutes with an interval of 30 minutes, it can be seen that the dust cleaning process runs 2 times. After the cleaning process is running the data shows that the dust density can drop to 0.16 mg/m³. Likewise, the temperature inside the engine panel, after the air circulation process runs well in the first or second conditions, the temperature inside the panel can drop below 40°C. From the test results, it can be seen that the system can work well.